Validation of a sports nutrition knowledge questionnaire for athletes in the United Kingdom and Ireland - Caitlin Edmonds; Ryan Tam; Sharon Madigan; Louise Gubb; Kathryn L. Beck; Janelle A. Gifford; Victoria M. Flood; Tania Prvan; Luke N. Gemming; Helen O'Connor (Journal of Nutritional Science, 2023)
Sound general and sports nutrition knowledge in athletes is essential for making appropriate dietary choices. Assessment of nutrition knowledge enables evaluation and tailoring of nutrition education. However, few well-validated tools are available to assess nutrition knowledge in athletes. The objective of the present study was to establish the validity of the Platform to Evaluate Athlete Knowledge Sports – Nutrition Questionnaire (PEAKS-NQ) for use in the United Kingdom and Irish (UK-I) athletes. To confirm content validity, twenty-three sports nutritionists (SNs) from elite, UK-I sports institutes provided feedback on the PEAKS-NQ via a modified Delphi method. After minor changes, the UK-I version of the PEAKS-NQ was administered to UK-I SN from the British Dietetic Association Sport and Exercise Nutrition Register, and elite athletes (EA) training at elite sports institutes in the UK and Ireland. Independent samples t-test and independent samples median tests were used to compare PEAKS-NQ total and subsection scores between EA and SN (to assess construct validity). Cronbach's alpha (good ≥ 0⋅7) was used to establish internal consistency. The SN achieved greater overall [SN (n 23) 92⋅3 (9⋅3) v. EA (n 154): 71⋅4 (10⋅0)%; P < 0⋅001] and individual section scores (P < 0⋅001) except Section B, Identification of Food Groups (P = 0⋅07). Largest knowledge differences between SN and EA were in Section D, Applied Sports Nutrition [SN: 88⋅5 (8⋅9) v. EA: 56⋅7 (14⋅5)%; P < 0⋅00]. Overall ES was large (2⋅1), with subsections ranging from 0⋅6 to 2⋅3. Cronbach's alpha was good (0⋅83). The PEAKS-NQ had good content and construct validity, supporting its use to assess nutrition knowledge of UK-I athletes.